2016
DOI: 10.5152/iao.2016.510
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implant Evaluation: Prognosis Estimation by Data Mining System

Abstract: OBJECTIVE:Prediction of speech recognition (SR) and quality of life (QoL) outcomes after cochlear implantation is one of the most important challenges for otologists. By sifting through very large amounts of data, data mining reveals trends, patterns, and relationships that might otherwise have remained undetected. There are identifiable pre-implantational factors that condition the cochlear implantation outcome. Our objective is to design a data mining system to predict and classify cochlear implant (CI) pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
1
12
1
Order By: Relevance
“…In the current study, GBI showed a general benefit of 24.81 points post-CI. This score was slightly lower when compared with previous work presented by Aimoni et al (70), who presented a mean GBI score of 33.5 in 53 subjects with bilateral hearing loss, and Guerra-Jiménez et al (69), who observed a mean GBI score of 36 in 29 subjects with bilateral hearing loss (69,70). This was not surprising considering that adults with SSD participate in society using monaural cues, thereby reducing the impact that their hearing loss has on their overall health status.…”
Section: Functional Hearing Benefitscontrasting
confidence: 66%
“…In the current study, GBI showed a general benefit of 24.81 points post-CI. This score was slightly lower when compared with previous work presented by Aimoni et al (70), who presented a mean GBI score of 33.5 in 53 subjects with bilateral hearing loss, and Guerra-Jiménez et al (69), who observed a mean GBI score of 36 in 29 subjects with bilateral hearing loss (69,70). This was not surprising considering that adults with SSD participate in society using monaural cues, thereby reducing the impact that their hearing loss has on their overall health status.…”
Section: Functional Hearing Benefitscontrasting
confidence: 66%
“…Although many patient-specific factors are thought to be associated with these outcomes, the strength of the associations of these factors with CI speech-recognition outcomes has been equivocal. For example, Kim et al and Francis et al both showed that older age at implantation was associated with poorer postimplant speech recognition abilities as compared with younger CI users, whereas Park et al and Guerra-Jimenez et al did not report this association. Similar inconsistencies exist for the majority of patient-specific factors that have been studied and reported.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent decade, AI based approaches have demonstrated their supreme capability over traditional signal processing algorithms in computer vision, natural language processing, gaming, and biomedical engineering, including hearing healthcare [9]. Machine learning and deep learning have changed various aspects of the 'AI + CI' research [10], including prognosis estimation [11], electrode placement [12], robotic surgery [13], mapping [14], [15], and sound signal processing [16], [17]. In addition, the successful stories of deep learning in general audio processing [18], [19] and hearing aids [20], [21] may also significant change the related field of CI sound processing.…”
Section: Introductionmentioning
confidence: 99%